2020
DOI: 10.24041/ejmr2020.27
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Conservative Management Versus Ultrasound Guided Aspiration of Small Amoebic Liver Abscess

Abstract: To compare the outcome of patients undergoing conservative management versus ultrasound guided aspiration of small amoebic liver abscess (=<200ml). This observational prospective study was conducted on 60 patients, aged between 18 to 80 years,After confirming the diagnosis, patients were exposed to medical management or USG guided Aspiration. Patients coming for regular follow-up after completing treatment were included in the study. It was found that the majority of the patients were male (86.7%) and with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…[31][32][33] The present study results showed all the cases to have reduction in volume on USG, Musa et al study on this dimension showed recurrence of abscess in conservative management was in 6 (20.0%) and need for surgical intervention was in 4 (13.3%) patients while in USG guided aspiration group only 1 (3.3%) patient showed recurrence. 34 The distribution of no of hospital days where most of the cases fall in the range between 12-20 days category for the present study, Bansal et al study in this dimension showed the hospital stay duration on average was 9.6 days which was more or less similar to this present study findings. Sharma et al study in same dimension showed the mean hospital stay of patients was 13.4 days which was not in conformity of the present study.…”
Section: Discussionsupporting
confidence: 88%
“…[31][32][33] The present study results showed all the cases to have reduction in volume on USG, Musa et al study on this dimension showed recurrence of abscess in conservative management was in 6 (20.0%) and need for surgical intervention was in 4 (13.3%) patients while in USG guided aspiration group only 1 (3.3%) patient showed recurrence. 34 The distribution of no of hospital days where most of the cases fall in the range between 12-20 days category for the present study, Bansal et al study in this dimension showed the hospital stay duration on average was 9.6 days which was more or less similar to this present study findings. Sharma et al study in same dimension showed the mean hospital stay of patients was 13.4 days which was not in conformity of the present study.…”
Section: Discussionsupporting
confidence: 88%
“…PCD-related complications were major issues in previous reports [17]. There were no significant complications found due to PCD in this study.…”
Section: Table 3: Distribution Of Amoebic Etiology and Right Lobe Involvement In Different Treatment Strategies Discussionsupporting
confidence: 41%
“…Most of these studies were conducted before the widespread use of PCD for the treatment of liver abscesses. Results of these studies showed that PNA was more useful in higher abscess volume [15][16][17]. In this study, conservative management was non-inferior to PNA for the duration of hospitalization and duration of antibiotics used even when abscess volume was similar in both groups (130.8±72.9 vs 177.2±129.5 ml, p = 0.27).…”
Section: Table 3: Distribution Of Amoebic Etiology and Right Lobe Involvement In Different Treatment Strategies Discussionmentioning
confidence: 67%
“…These studies were mostly before gaining the popularity of PCD. Results of these studies showed that PNA was more useful in higher abscess volume (15,16,17). In this study, conservative management was non-inferior to PNA with respect to duration of hospitalization and duration of antibiotics used even when abscess volume was similar in both groups (130.8 ± 72.9 vs 177.2 ± 129.5 ml, p = 0.27).…”
Section: Discussionmentioning
confidence: 52%